Goosebumps A shocker on Shock Street - Stine, R. L. (Scholastic Inc. New York, N.Y., 2015)
Erin Wright and her best friend Marty love The Shocker on Shock Street movies, but get the scare of their lives when they visit the new Shocker Studio Theme Park